Método total physical response (t.p.r.) y su influencia en el proceso de enseñanza-aprendizaje del vocabulario (vocabulary) del idioma ingles en los estudiantes del noveno año de la unidad educativa “Oswaldo Villamil auz” del cantón Quevedo año 2015 - Guevara Guevara, Absalón Kennedy (2015)
This research aims to be an important contribution to the development of learning English as a second language and also help the student to be the author of their own learning through different techniques. This research is relevant and meets the necessary requirements for teachers to suit their needs. After obtaining information through direct observation and surveys regarding the incidence of "Total Physical Response Method" to develop vocabulary skills (vocabulary) English language students of seventh year basic education "Oswaldo Villamil auz "it identified that students had the desire to learn to express themselves in this language, but activities within the classroom were not appropriate for students to develop in a sound and efficient manner. the use of vocabulario (vocabulary) and speaking activities (dialogues, role-plays, conversations, songs, videos) by the teacher as well as the absence of headings for the student to strengthen their shortcomings in learning was not found. To solve this problem the development of a training manual for the development of vocabulario (vocabulary) and speaking skills of English as a second language, using different techniques in which students can develop in a different way and thus motivate students was necessary develop these skills, thus contributing to increasing the teaching and learning process to achieve a high level of competitiveness in the students of this institution. K